A RELATIVE STUDY TO FIND OUT THE RISK POPULATION IN VINDHYAN REGION BY CARCINOGEN ACTIVATING AND DEACTIVATING THE GSTM1 POLYMORPHISM - Pandey, Snehlata; Indurkar, Pallavi; Tripathi, Arvind; Thipathi, Jitendra; Dubey, Sanjeev (International Journal of Research -GRANTHAALAYAH, 2016)
The Glutathione S-transferase are a family of phase II isoenzymes, believed to protect cells from reactive chemical intermediates and oxidative stress, resulting from a wide range of electrophilic xenobiotics (Example-PAH) and endogenous intermediates. Inheritance of null (gene deletion) alleles of the GSTM1 (chromosome 1p 13.3) genes is common in the population varies by ethnicity and is associated with the loss of enzymatic activity and cytogenetic damage. The studies have linked the gene deletion of GSTM1 to susceptibility to various cancers, including lung, bladder, Head, Neck, Colon and basal cell carcinoma. Variation in metabolism of carcinogens could increase or decrease exposure of cells to carcinogens. Ethnic variation in cancer incidence and mortality may be due in part because of differences in the distribution of polymorphisms, as well as differences in environmental and dietary exposures.